Postoperative radiotherapy and the role of regional lymph node Irradiation in localized Merkel cell carcinoma: a single-center retrospective analysis - Dinges, Lisa A.; Eichkorn, Tanja; Regnery, Sebastian; Hörner-Rieber, Juliane; Debus, Jürgen; Hassel, Jessica C.; Uzun-Lang, Kristin (Cancers, 2022)
The aim of this study was to analyze the pattern of relapse of patients with Merkel cell carcinoma (MCC) that underwent resection of the primary tumor site and postoperative radiotherapy at the Department of Radiation Oncology of Heidelberg University and to determine the role of the elective radiotherapy of regional lymph nodes with respect to SLNB results. A total of 57 patients were included in the present retrospective analysis. A total of 33 patients had additional lymph node irradiation (LNI); 24 had postoperative radiotherapy of the tumor bed only. Median follow-up was 43 months. Recurrence rate of the total cohort was 22.8%. Most relapses (69%) occurred in the regional nodes. Cumulative infield-tumor recurrence rate was low with 5.3%. Regional recurrence was more frequent in the cohort without LNI with 85.7% versus 37.5% with LNI. These results were similar for patients with negative sentinel lymph node (SLN) only with 80% regional relapses for those without LNI versus 33% with LNI. In conclusion, our data show that regional recurrence is the most frequent site of relapse in stage I-III MCC treated with curative intended postoperative radiotherapy and that elective irradiation of the regional lymph nodes reduces the risk of regional relapse even if the SLN was negative.
Gesehen am 08.11.2023